Four minor prophets Obadiah, Jonah, Habakkuk and Haggai : their message for today - Gaebelein, Frank Ely, 1899-1983 (Chicago, IL Moody, 1970)
Includes bibliographical references.
Keywords: Bible. O.T. Minor Prophets -- commentaries